2001
DOI: 10.1021/ja010673x
|View full text |Cite
|
Sign up to set email alerts
|

N-Confused Expanded Porphyrin:  First Example of a Modified Sapphyrin with an Inverted N-Confused Pyrrole Ring

Abstract: Research on synthesis of porphyrin isomers has gained momentum since the discovery of porphycene 1 by Vogel and coworkers and N-confused porphyrin 2 independently by Furuta et al. and Latos-Grazynski and co-workers. The other porphyrin isomers reported to date include, corrphycene, 3 hemiporphycene, 4 and isoporphycene 5 obtained by shuffling the four pyrrolic subunits and meso-carbon bridges. Extensive studies on Nconfused porphyrin 1 2 and doubly N-confused porphyrin 2 6 have witnessed unusual metalation che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
1
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 15 publications
(26 reference statements)
0
54
1
3
Order By: Relevance
“…[76] Condensation of either heterobipyrrole 49 or 49 b with the "N-confused" tripyrrane 62 followed by oxidation gives rise to 63 a or 63 b in a yield of 24 or 30 %, respectively (Scheme 13). As might have been anticipated based on the conformational behavior of the related heteroatom sapphyrins 51 a-f and 59 a-e, the so-called confused pyrrolic subunits in 63 a and 63 b were found to be inverted.…”
Section: N-confused Heterosapphyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…[76] Condensation of either heterobipyrrole 49 or 49 b with the "N-confused" tripyrrane 62 followed by oxidation gives rise to 63 a or 63 b in a yield of 24 or 30 %, respectively (Scheme 13). As might have been anticipated based on the conformational behavior of the related heteroatom sapphyrins 51 a-f and 59 a-e, the so-called confused pyrrolic subunits in 63 a and 63 b were found to be inverted.…”
Section: N-confused Heterosapphyrinsmentioning
confidence: 99%
“…Front (top) and side (bottom) views of the solid-state structure of 63 a. [76] that this proton is located on the nitrogen atom of the Nconfused pyrrolic ring in solution, at least in CDCl 3 and [D 8 ]toluene. However, this results in a structure in which the heterosapphyrin is cross-conjugated (tautomer 63 a), rather than one wherein a classic 22 p-electron aromatic pathway, characteristic of all other heterosapphyrins reported to date, prevails (tautomer 63 a').…”
Section: N-confused Heterosapphyrinsmentioning
confidence: 99%
“…[9] Previously, we and the Chandrashekar research group reported diselena and dithia derivatives of N-confused meso-aryl sapphyrin; [10] however, the genuine meso-aryl N-confused sapphyrin remains an important synthetic target to clarify the intrinsic role of the confused pyrrole unit in the pentapyrrolic macrocycle. Herein we report the first synthesis of N-confused all-aza-meso-aryl sapphyrin (NC-Sap) and N-fused sapphyrin (NF-Sap), and demonstrate the utility of the confusion approach in synthesizing porphyrin analogues.…”
mentioning
confidence: 99%
“…[11] This tautomeric form is different from that of the previously reported dithiasapphyrin, which takes a less aromatic form. [5,10] For 1, in accordance with the tautomeric structure above, a 22p aromatic system is indicated by the difference in the chemical shifts between the outer and inner protons (Dd = 12.6 ppm) in 1, which is slightly less than that of the all-aza-meso-tetrakis(pentafluorophenyl)sapphyrin (Dd = 14.8 ppm), [11] but much higher than that of N-confused dithiasapphyrin (Dd = 7.06 ppm) [10] and the recently reported inverted b-alkylated sapphyrin (Dd = 4.79 ppm). [13] Reflecting the aromatic nature of 1, two intense bands are observed in the Soret region at 395 and 497 nm in the absorption spectrum, and four small Q-type bands are observed at 625, 679, 750, and 871 nm (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation